2017
DOI: 10.1158/1541-7786.mcr-16-0191
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Promote Ovarian Cancer Cell Invasion through Transfer of CD44 to Peritoneal Mesothelial Cells

Abstract: Mechanistic insight from the current study suggests that therapeutic targeting of exosomes may be beneficial in treating ovarian cancer. Mol Cancer Res; 15(1); 78-92. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 46 publications
4
158
0
1
Order By: Relevance
“…CD44 is upregulated in cancer stem cells, regulates adhesion and metastasis, and it is a well-known metastatic marker in exosomes (Senbanjo & Chellaiah, 2017). It was found to be delivered from ovarian cancer cells to mesothelial cells where it upregulates degradation of the ECM by inducing gene expression of MMPs to promote cancer cell invasion (Nakamura et al, 2017). A specific involvement of changes in the miRNA profile, either induced by CD44 or due to RNA transported by exosomes was not noted.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…CD44 is upregulated in cancer stem cells, regulates adhesion and metastasis, and it is a well-known metastatic marker in exosomes (Senbanjo & Chellaiah, 2017). It was found to be delivered from ovarian cancer cells to mesothelial cells where it upregulates degradation of the ECM by inducing gene expression of MMPs to promote cancer cell invasion (Nakamura et al, 2017). A specific involvement of changes in the miRNA profile, either induced by CD44 or due to RNA transported by exosomes was not noted.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…CD44 expression is upregulated under the postoperative inflammatory response, which involves elevated levels of reactive oxygen species, transforming growth factor-β1 (TGF-β1), interleukin-1β and tumor necrosis factor-α, leading to enhancement of cancer cell adhesion (32). Recently, Nakamura et al (33) co-cultured human peritoneal mesothelial cells (HPMCs) with exosomes derived from ovarian cancer cells and observed that HPMCs, which internalized TEX, exhibited higher level of CD44 expression and underwent mesothelial-to-mesenchymal transition (MMT). Additionally, CD44 overexpression in HPMCs promoted cancer invasion by inducing the HPMCs to secrete MMP9, in order to cross the mesothelial barrier.…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%
“…Additionally, CD44 overexpression in HPMCs promoted cancer invasion by inducing the HPMCs to secrete MMP9, in order to cross the mesothelial barrier. By contrast, by knockdown of CD44 expression, TEX exerted fewer effects on HPMCs (33). Similarly, isolated exosomes from human gastric cancer cells have demonstrated expression of CD44H and CD44 variant exon 6 isoforms, which may serve a role in the attachment of TEX to cancer cells (34).…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%
“…The pathogenesis of PF is characterized by a decreasing number of mesothelial cells and progressive submesothelial thickening with an increasing myofibroblast presence [23]. The accumulation of collagenproducing fibroblasts and excessive deposition of ECM disrupt normal peritoneal architecture and homeostasis [24].…”
Section: Molecular Network Of Fibrosis and Angiogenesis In Modulatingmentioning
confidence: 99%